1993
DOI: 10.1590/s0036-46651993000200002
|View full text |Cite
|
Sign up to set email alerts
|

Chronic gastritis and Helicobacter pylori in digestive form of Chagas' disease

Abstract: Patients with the digestive form of Chagas' disease frequently present chronic gastritis. As the microorganism Helicobacter pylori is now accepted as the most common cause of human chronic gastritis, the present work was undertaken to verify a possible relationship between the presence of this bacterium and inflammatory changes of antral mucosa in chagasic patients. Seventeen chagasics, with megaesophagus and or megacolon were studied. Fragments from two different regions of antral mucosa were obtained by endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
3
10
1
Order By: Relevance
“…We found a high prevalence of gastritis and H. pylori infection in both groups of chagasic and non-chagasic patients in the present study. Although two previous studies have reported similar fi ndings for a small group of chagasic patients 13,14 , this is the fi rst controlled study to demonstrate that H. pylori is the major cause of gastritis in patients with Chagas disease.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…We found a high prevalence of gastritis and H. pylori infection in both groups of chagasic and non-chagasic patients in the present study. Although two previous studies have reported similar fi ndings for a small group of chagasic patients 13,14 , this is the fi rst controlled study to demonstrate that H. pylori is the major cause of gastritis in patients with Chagas disease.…”
Section: Discussionsupporting
confidence: 56%
“…A fi rst basal breath sample was collected, and then, an oral dose of 75mg of 13 C-urea dissolved in 200mL of orange juice was administered. An additional breath sample was collected after 30min.…”
Section: C-urea Breath Testmentioning
confidence: 99%
See 1 more Smart Citation
“…After the discovery of H. pylori in 1982, Barbosa et al 13 were the first to investigate the presence of bacteria in the gastric mucosa of patients with Chagas disease, followed by Oliveira et al, who evaluated patients with the digestive and indeterminate clinical forms of the disease, respectively. In those studies, the prevalence of H. pylori infection was very high (~95%).…”
Section: Discussionmentioning
confidence: 99%
“…Later, some studies demonstrated a high prevalence of H. pylori infection in patients with Chagas disease [13][14][15][16] . As this small number of studies on T. cruzi and H. pylori co-infection had no control groups and/or included a low number of patients, we evaluated the prevalence of H. pylori infection among chagasic and non-chagasic subjects living in a region previously considered endemic for Chagas disease.…”
Section: Introductionmentioning
confidence: 99%